2007
DOI: 10.1017/s0967199407004327
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of ovarian follicles in the caeciliansIchthyophis tricolorandGegeneophis ramaswamii:light and transmission electron microscopic study

Abstract: Though much is known about various aspects of reproductive biology of amphibia, there is little information on the cellular and mechanistic basis of assembly of ovarian follicles in this group. This is especially true of the caecilians. Therefore, taking advantage of the abundant distribution of caecilians in the Western Ghats of India, two species of caecilians, Ichthyophis tricolor and Gegeneophis ramaswamii, were subjected to light and transmission electron microscopic analysis to trace the sequential chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 63 publications
(93 reference statements)
0
9
0
3
Order By: Relevance
“…The sequential cytological changes in the two caecilians from these perspectives are believed to be comparable with those known for the anurans X. laevis (Dumont 1972;Wallace and Bergink 1974;Wallace 1985;Wallace and Selman 1990), Rana esculenta (Wartenberg and Gusek 1960), Rana pipiens (Ward 1962) and Rana tigrina (Sretarugsa et al 2001) and the urodeles Notophthalmus viridescens (Hope et al 1963) and Necturus maculosus (Kessel and Ganion 1980). The formation of the vitelline envelope in X. laevis (Dumont 1972) and R. tigrina (Sretarugsa et al 2001) is first detectable in stage II oocytes as is the case in the caecilians (Beyo et al 2007a(Beyo et al , 2007b. However, a study in X. laevis (Yamaguchi et al 1989) has indicated that the cytoplasm of oocytes as early as stage I contains components reacting to anti-vitelline coat antibodies, suggesting that the oocyte plays a role in synthesizing its own vitelline envelope.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…The sequential cytological changes in the two caecilians from these perspectives are believed to be comparable with those known for the anurans X. laevis (Dumont 1972;Wallace and Bergink 1974;Wallace 1985;Wallace and Selman 1990), Rana esculenta (Wartenberg and Gusek 1960), Rana pipiens (Ward 1962) and Rana tigrina (Sretarugsa et al 2001) and the urodeles Notophthalmus viridescens (Hope et al 1963) and Necturus maculosus (Kessel and Ganion 1980). The formation of the vitelline envelope in X. laevis (Dumont 1972) and R. tigrina (Sretarugsa et al 2001) is first detectable in stage II oocytes as is the case in the caecilians (Beyo et al 2007a(Beyo et al , 2007b. However, a study in X. laevis (Yamaguchi et al 1989) has indicated that the cytoplasm of oocytes as early as stage I contains components reacting to anti-vitelline coat antibodies, suggesting that the oocyte plays a role in synthesizing its own vitelline envelope.…”
Section: Discussionmentioning
confidence: 56%
“…The two caecilians, which overlap in their distribution in the Western Ghats of Southern India, differ little in their reproductive cyclicity, structural changes in the ovarian follicles and dependence on environmental factors (Beyo et al 2007a(Beyo et al , 2007b. Hence, we have traced the developmental sequence of the follicle cell/oocyte interface for these two species together.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations